PENGGUNAAN TEACHING AT THE RIGHT LEVEL (TARL) DALAM PENYESUAIAN TINGKAT KESULITAN ASESMEN UNTUK MENINGKATKAN HASIL BELAJAR - Alfa Cos Sinaga Adhiya; Dwi Heryanto; Endang Johani S (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
This research aims to evaluate the effectiveness of the Teaching at the Right Level (TaRL) approach in improving student learning outcomes by paying attention to achievement levels. The problem raised is how the division of students' achievement levels (high, medium and low) can influence understanding and achievement of learning outcomes through adjusting the level of difficulty of the questions. The method used is classroom action research by dividing students into three groups based on the level of student achievement. Each group is given questions adjusted to the level of difficulty relevant to the level of the students. Learning outcome data was collected through pre-test and post-test evaluations to measure the increase in students' abilities after implementing this approach. The research results show that the application of TaRL by dividing achievement levels and adjusting the difficulty level of questions significantly improves student learning outcomes. The group with low achievement levels showed significant progress in understanding the material, while the groups with high and medium achievement levels also experienced positive improvements. This research recommends using the TaRL approach in learning practices to optimize learning outcomes at various levels of student achievement.